Molecular Docking Chlorogenic Acid and Isomer Compound as Cyclooxygenase-2 (COX-2) Inhibitor in Atherosclerosis - Nurarifa, Ratna; Rachmawati, Devi Era; Utari, Dwi (JSMARTech: Journal of Smart Bioprospecting and Technology, 2020)
Atherosclerosis is an inflammatory disease caused by oxidized LDL. Chloroghenic acid (CGA) is a polyphenol compound and its isomers such as Caffeoylquinic acid (CQA) and Feruloylquinic acid (FQA) can increase the activity of antioxidant activity and can significantly reduce total cholesterol in the blood. Cyclooxygenase (COX) is an enzyme that correlates with the inflammatory process. COX is divided into two isoforms, COX-1 and COX-2. Prostanoid synthesis via the action of cyclooxygenase-2 (COX-2) is a component of the inflammatory response. All prepared compound of Chlorogenic acid (CGA) and its isomer, Caffeolycquinic acid (CQA) and Feruloylquinic acid (FQA) is used for molecular docking by using HEX 8.0.0. Visualization process is done by using Discovery Studio Client 4.1 software. The results showed docking between COX-2 with CGA compounds and its isomers also drug Ibuprofen shows energy binding COX-2 - CGA of -320 kcal / mol, COX-2 - CQA of -298 kcal / mol, COX-2 - FQA of -282 kcal / mol, and COX-2 - Ibuprofen of -230 kcal / mol. The docking results show the CGA compound and its isomers have smaller energy bindings than the drug Ibuprofen. This shows that the CGA compound and its isomers are better than the Ibuprofen drug so that it has the potential as an anti-inflammatory which can be used to prevent the formation of atherosclerosis.